2018
DOI: 10.1007/s10803-018-3680-0
|View full text |Cite
|
Sign up to set email alerts
|

McGurk Effect by Individuals with Autism Spectrum Disorder and Typically Developing Controls: A Systematic Review and Meta-analysis

Abstract: By synthesizing existing behavioural studies through a meta-analytic approach, the current study compared the performances of Autism spectrum disorder (ASD) and typically developing groups in audiovisual speech integration and investigated potential moderators that might contribute to the heterogeneity of the existing findings. In total, nine studies were included in the current study, and the pooled overall difference between the two groups was significant, g = - 0.835 (p < 0.001; 95% CI - 1.155 to - 0.516). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
5
22
0
1
Order By: Relevance
“…These findings indicate that the visual perception of individuals with ASD or higher levels of autistic traits were less affected by auditory information, suggesting a difficulty in integrating audio-visual information. Consistent with this, a recent meta-analysis reported that people with ASD were less likely to experience the McGurk effect, an index of multisensory integration, compared with TD individuals (Zhang et al 2019). Several studies have demonstrated that adults with ASD garnered less additional benefit from audio-visual information when distinguishing or identifying emotions (Charbonneau et al 2013;Xavier et al 2015).…”
Section: Discussionmentioning
confidence: 73%
“…These findings indicate that the visual perception of individuals with ASD or higher levels of autistic traits were less affected by auditory information, suggesting a difficulty in integrating audio-visual information. Consistent with this, a recent meta-analysis reported that people with ASD were less likely to experience the McGurk effect, an index of multisensory integration, compared with TD individuals (Zhang et al 2019). Several studies have demonstrated that adults with ASD garnered less additional benefit from audio-visual information when distinguishing or identifying emotions (Charbonneau et al 2013;Xavier et al 2015).…”
Section: Discussionmentioning
confidence: 73%
“…As the wide-ranging implications of MSI alterations in autism have become more apparent, studies using a variety of different paradigms to evaluate this area of functioning have emerged. Some such approaches have included complex stimuli and task demands, like the ability to integrate audiovisual information to process emotional expressions 21 , the speech-in-noise paradigm 22,23 , and the McGurk effect task 2430 . Other researchers have investigated the issue using more simple approaches using non-social stimuli, such as the flash-beep illusion task 3134 , and visual search tasks 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with ASD are less susceptible to the speech related McGurk illusion (Taylor et al, 2010; Bebko et al, 2014; Stevenson et al, 2014) and show lower sensitivity for temporal synchrony of AV speech events (Bebko et al, 2006). But the picture is not fully consistent (Zhang et al, 2018). Studies exist showing no differences in AV speech perception between ASD and typically developed subjects (Williams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%